2018
DOI: 10.3847/2041-8213/aae713
|View full text |Cite
|
Sign up to set email alerts
|

Mode Changing and Giant Pulses in the Millisecond Pulsar PSR B1957+20

Abstract: Many radio pulsars have stable pulse profiles, but some exhibit mode changing where the profile switches between two or more quasi-stable modes of emission. So far, these effects had only been seen in relatively slow pulsars, but we show here that the pulse profile of PSR B1957+20, a millisecond pulsar, switches between two modes, with a typical time between mode changes of only 1.7 s (or ∼ 1000 rotations), the shortest observed so far. The two modes differ in both intensity and polarization, with relatively l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Figure 13 plots fluence distribution for both MP and IP GPs. Mahajan et al (2018) observed the original Black Widow Pulsar B1957+20 in 311. 25-359.25 ṀHz frequency range at the Arecibo Observatory.…”
Section: Appendix A: Details On Fluence Distributions From the Litera...mentioning
confidence: 99%
“…Figure 13 plots fluence distribution for both MP and IP GPs. Mahajan et al (2018) observed the original Black Widow Pulsar B1957+20 in 311. 25-359.25 ṀHz frequency range at the Arecibo Observatory.…”
Section: Appendix A: Details On Fluence Distributions From the Litera...mentioning
confidence: 99%
“…While common in slow pulsars, phenomena similar to mode changes have been reported in only two millisecond pulsars till date. A periodic change in the profile over a timescale of about 2 s was reported for the first-detected black widow pulsar, PSR B1957+20 (Mahajan et al 2018). A distinct profile change was reported in PSR J1643−1224 around MJD 57074 by Shannon et al (2016), which introduced systematics in the timing residuals of this pulsar at 10 cm and 20 cm bands.…”
Section: Introductionmentioning
confidence: 78%
“…Thus GReX should detect some of the brightest super-giant pulses from Crab-like pulsars in our Galaxy and nearby. It is also salient that some GRP-emitting pulsars exhibit a "kink" in their energy distribution, such that the powerlaw N (> F th ) flattens in the high-energy tail, making ultra-bright bursts more common (Mahajan et al 2018).…”
Section: Galactic Magnetarsmentioning
confidence: 99%